Prospective Validation of CD-62L (L-Selectin) as Marker of Durable Response to Infliximab Treatment in Patients With Inflammatory Bowel Disease: A 5-Year Clinical Follow-up. Issue 2 (15th February 2021) - Bravo, Francisco; Macpherson, Jamie A.; Slack, Emma; Patuto, Nicolas; Cahenzli, Julia; McCoy, Kathy D.; Macpherson, Andrew J.; Juillerat, Pascal; ,
Abstract : INTRODUCTION: The development of biomarkers to guide management of anti–tumor necrosis factor (TNF) agents in patients with inflammatory bowel disease (IBD) is an unmet need. We developed an in vitro blood assay to predict patient long-term outcome with the anti-TNFα agent infliximab (IFX). METHODS: Patients with IBD were classified according to the shedding of an L-selectin (CD62L) from the surface of their granulocytes in whole blood. CD62L shedding was quantified by flow cytometry before and after drug administration. A clinical data collection from June 2012 to August 2017 with blinded IFX management was aimed at validating the long-term predictive value of this test. RESULTS: Among 33 patients with IBD (17 Crohn's disease and 5 ulcerative colitis), 22 were predicted functional responders (PFR) and 11 were predicted as nonresponders (NR) according to the in vitro test. Five years after study initiation, 72% of PFR were still treated with IFX (vs 27% in the NR group; P < 0.05), with a median time spent under IFX of 45 vs 12 months ( P = 0.019), respectively. Thirty-five medicosurgical events occurred with a median time to first event of 3 vs 30 months ( P = 0.023), respectively. Our assay was the best independent predictor of staying long term on IFX ( P = 0.056). DISCUSSION: An assay-based in vitro test for functional blockade of TNFα (CD62L shedding) provides an excellent long-term (at 3–5 years) independent predictor of durable use of IFX in patients with IBD. Testing patients could personalize decision making to significantly reduce costs and risk of adverse events and complications.